2022
DOI: 10.29196/jubpas.v30i4.4480
|View full text |Cite
|
Sign up to set email alerts
|

Production and Purification of Laccase enzyme by Trichoderma viride

Abstract: The ability of Trichoderma viride to synthesize extracellular enzymes (Lacase enzyme) using a substrate that contains media was examined. This isolate generated laccase at its greatest level (0.166U/ml) in liquid medium.  This study was  demonstrated the production, purification, and characterisation of the laccase enzyme from T.viride. The results showed that 96 hours was the optimum period of time for Laccase to incubate from this fungus. Laccase displayed the maximum level of activity at pH 4.5 and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…The highest laccase production was 2.89 U/ml (predicted value of 2.71 U/ml) obtained in the run (6) with shaking fermentation at 25 °C and pH 7 after 8 days using a 2% inoculum size of 50 ml fermentation medium involving 1.5% glucose, 0.6% peptone, 0.1% KH 2 PO 4 , 0.01% K 2 HPO 4, and 50 μg/l guaiacol. After optimization, the laccase activity recorded in our study was higher than those recorded by Mohsen et al [62], who obtained 1.03 U/ml laccase from Trichoderma viride after 96 h of incubation at 30 °C, Umar [43] found that the highest laccase activity from T. atroviride was 2.62 U/ml. After the laccase optimization process, Jenefar et al [73] obtained 2.3 U/ml laccase from Perenniporia subtephropora using medium initial pH 6 and incubation at 30 °C, while Sadhasivam et al [74] utilized Trichoderma harzianum by augmented 1 mM CuSO 4 and found that the highest yield of laccase activity reached 4.36 U/ml after 4 days.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The highest laccase production was 2.89 U/ml (predicted value of 2.71 U/ml) obtained in the run (6) with shaking fermentation at 25 °C and pH 7 after 8 days using a 2% inoculum size of 50 ml fermentation medium involving 1.5% glucose, 0.6% peptone, 0.1% KH 2 PO 4 , 0.01% K 2 HPO 4, and 50 μg/l guaiacol. After optimization, the laccase activity recorded in our study was higher than those recorded by Mohsen et al [62], who obtained 1.03 U/ml laccase from Trichoderma viride after 96 h of incubation at 30 °C, Umar [43] found that the highest laccase activity from T. atroviride was 2.62 U/ml. After the laccase optimization process, Jenefar et al [73] obtained 2.3 U/ml laccase from Perenniporia subtephropora using medium initial pH 6 and incubation at 30 °C, while Sadhasivam et al [74] utilized Trichoderma harzianum by augmented 1 mM CuSO 4 and found that the highest yield of laccase activity reached 4.36 U/ml after 4 days.…”
Section: Discussioncontrasting
confidence: 80%
“…Umar [43] evaluated ten Trichoderma species for laccase production and found that T. atroviride was the highest producer with 2.62 U/ml. Mohsen et al [62] obtained 0.266 U/ml laccase from Trichoderma viride using 0.02% guaiacol after 96-h incubation at 28 °C. Abd El Monssef et al [63] reported that Trichoderma harzianum produced 1.286 U/ml after 6 days of incubation at 30 °C using a medium supplemented by 0.04% guaiacol and an initial pH of 5.5.…”
Section: Discussionmentioning
confidence: 99%